Penyelesaian Tapal Batas Desa Antara Desa Bukit Makmur dan Desa Kaliorang Kecamatan Kaliorang Kabupaten Kutai Timur - Yufani Battista Rossi; Muhammad Jamal Amin; Nur Hasanah (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2021)
Completion of inter-Village boundaries is a procedure that includes the determination, confirmation and ratification of village boundaries realized by the Village Boundary Affirmation and Determination Team (PPB Des Team), referring to the mechanism that has been inaugurated in PERMENDAGRI Number 45 of 2016. This research uses qualitative methods, looking at the process of establishing, confirming and validating the village PPB Team as well as the obstacles during the process of finalizing the boundaries. The purpose of this descriptive research is to explain in an orderly and interrelated, factual, and accurate manner the facts and the research process. The results showed that the settlement of the village boundary between Bukit Mamur Village and Kaliorang Village had been completed. The inhibiting factor in the settlement of boundaries was the lack of good communication between village officials and the lack of human resources in completing village boundaries, besides that, there were not many authentic documents that accommodated the process of document research and making work maps and overlapping boundaries between Kaliorang and Kaubun districts. The supporting factors in settling village boundaries between Bukit Makmur Village and Kaliorang Village are the existence of a dispute relationship between Bumi Sejahtera Village and Kaliorang Village, and the participation of all elements of society in the stages of village boundary settlement.